The Effectiveness of Using the Make-A- Match Learning Model in Improving Mathematics Learning Outcomes in Elementary Schools: A Systematic Literature Review - Hani Savitriana; Berta Apriza; Darwanto (Universitas Pendidikan Ganesha, 2025)
Mathematics learning at the elementary school level plays a crucial role in developing students’ logical thinking, analytical skills, and problem-solving abilities to prepare them for future challenges. This study aims to analyze the effectiveness of the Make a Match learning method in enhancing mathematics learning outcomes through a systematic literature review approach. The method employed is a Systematic Literature Review (SLR) that analyzes various relevant empirical studies. The results indicate that the implementation of the Make a Match model significantly improves student motivation, active participation, and academic achievement in mathematics, as reflected in the increased average scores and mastery levels. The citation distribution shows fluctuations, peaking at 55% in 2021 and declining to 7% in 2024, despite the number of publications reaching 273 articles in 2024, indicating high research productivity and potential for increased citation impact in the future. The findings suggest that the Make a Match learning model can serve as an innovative alternative to optimize mathematics learning processes in elementary schools while supporting the development of 21st-century skills among students. Therefore, the Make a Match model is recommended as an effective strategy to improve mathematics learning outcomes at the elementary education level.